EFFECTIVENESS OF IMPLEMENTING HALAL CERTIFICATION ON MSME PRODUCTS IN LAMONGAN DISTRICT - Masruroh , Ainul; Afiyah , Siti (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This research aims to find out how effective the implementation of halal certification is for MSMEs in the Lamongan district using Lawrence M. Friedman's legal system theory which consists of substance, structure, and culture. This type of research is empirical juridical research, with a sociological juridical approach. The location of this research was carried out at MSMEs in Lamongan Regency. The type of data used is primary data from field studies and secondary data from literature searches related to the discussion. The results of the research are that the implementation of halal certification for MSME products in Lamongan is quite effective. Where substance Law No. 33 of 2014 concerning Halal Product Guarantees and the Job Creation Law are the basis for implementing halal certification and this is explained in various implementing regulations below. The institutionalization or legal institutions implementing halal certification start from BPJPH and MUI and other authorized institutions up to the Lamongan district level. Meanwhile, culturally there is support from MSME business actors because it is based on religious characteristics, legal awareness, awareness to improve product quality, and massive socialization and training carried out by the Lamongan Regency Regional Government. Apart from the large amount of community support, it can be seen from the number of organizations that have taken on the role of accompanying halal certification